Salivary rheumatoid factor in primary and secondary Sjögren’s syndrome - Triana Reyes, Silvia Arely; Martínez Sandoval, Gloria; Rodríguez Franco, Norma Idalia; Chapa Arizpe, María Gabriela; Rodríguez Pulido, Jesús Israel; Alcázar Pizaña, Andrea Guadalupe; Riega Torres, Janett Carmen Luzmila (Universidad de Concepción, 2019)
Sjögren's syndrome is a chronic autoimmune disease, characterized by the presence of hyposalivation and xerophthalmia, which in addition to other factors is diagnosed by the presence of rheumatoid factor in blood. The objective of the present study is to evaluate the presence of rheumatoid factor (IgG-IgM) in the saliva of patients with primary and secondary Sjögren's syndrome. Materials and methods: Forty samples from patients with primary and secondary Sjögren's syndrome previously diagnosed by the Arthritis and Rheumatism Specialist Center of the Autonomous University of Nuevo Leon were analyzed. Samples were taken from the saliva using the Carlson-Crittenden device to evaluate the IgG-IgM immunocomplex using the ELISA method. Results: No significant difference was found between the presence of IgM in primary (0.099±0.016) and secondary Sjögren syndrome (0.098±0.017), however, a high presence of IgG was found in the group of patients with secondary Sjögren's syndrome (0.134±0.054). Conclusion: The search for diagnostic tools using salivary biomarkers has come with economic and clinical advantages, however, in the present study no significant changes were found in salivary rheumatoid factor between both groups.